Developments in Automobile Emission Control - Abdulrahim, A. T.; Usmah, M.L.; Alkali, B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2004)
It is widely acknowledged that automobiles are becoming dominant contributors to atmospheric pollution in most of the world’s cities. Hence, the need to find effective methods of controlling automobile emissions becomes imperative. Available automobile emissions’ control measures which include various legislations and responses to legislations such as improvement in the state of the art controls, greater attention towards automobiles growth, improvement of engine design features, periodic tune-up, the use of alternative fuels and the development of non-fossil energy sources were reviewed in this paper.